Interrelations of various tree vitality indicators and their reaction to climatic conditions on a european beech (Fagus sylvatica L.) plot : Međuovisnost različitih indikatora vitaliteta stabala i njihov odziv na klimatske uvjete na plohi obične bukve (Fagus sylvatica L.) - Ognjenović, Mladen (Array, 2020)
Interrelations of various common beech vitality indicators (crown defoliation, foliar chemistry, radial growth) as well as their possible dependencies on climatic conditions were investigated over the course of 12 years in a mature and healthy beech stand. Our results confirm the importance of temperature variables for defoliation, as high temperatures during spring and summer months induce the increase of defoliation. The same negative influence was observed with high maximum temperatures and low precipitation during previous year summer months. Phosphorus, calcium and magnesium nutrition of beech trees suffers from high temperatures during current year summer and benefits from more precipitation. High temperatures in current year May positively influence beech radial growth, while a wide range of minimum temperatures during March and June has a negative effect. In summary, high summer temperatures and low precipitation were shown to have a negative effect on all vitality indicators, and for defoliation and nutrition this effect can last into the following year.